Suction effect on MHD flow of Brinkman-type fluid with heat absorption and first-order chemical reaction - Yao, Shao-Wen; Ahmad, Mushtaq; Inc, Mustafa; Ahmad, Ikhlaq; Asjad, Muhammad Imran; Nazar, Mudassar (Frontiers in Energy Research, 2022)
Suction/injection is a mechanical effect and used to control the energy loses in boundary layer region by reducing the drag on the surface. In this paper unsteady MHD flow of Brinkman type fluid with suction/injection, heat absorbtion and chemical reaction is investigated and analytical solution is established. The corresponding results for temperature,concentration and velocity fields are obtained with the help of Laplace transformation Method. The physical effects of thermal and mass Grashoff number, Prandtle number, Shmidt number, heat absorbtion parameter, first order chemical reaction parameter, suction/injection, Brinkman parameter and magnetic parameter have been discussed graphically.